Through the Glorieta Pass - Adams, Lavonne Jayne (Long Beach, California Pearl Editions, 2009)
Poems about the experiences of women who traveled westward, taking part in establishing the Santa Fe Trail.
How the earth became bountiful (A Cheyenne tale) -- Susan Magoffin -- How humans became mortal -- On the far side of Tucumcari Butte -- Anna Maria Morris -- Jicarilla Apache, shaping clay -- Marian Sloan -- Apache -- Kate Kingsbury -- Barter -- Murphy wagons -- Marian Sloan, return to Missouri -- Sioux -- Julia Anna Archibald -- Comet -- Wind Tamer -- Ernestine Huning -- Yellow-haired Woman, Cheyenne -- Photography, after the nun's death -- Sister Blandina -- Notes -- Bibliography.
"Winner of the 2007 Pearl Poetry Prize, selected by David Hernandez."
Includes bibliographical references (pages 62-64).
Winner of the 2007 Pearl Poetry Prize.
111107
Keywords: Women -- Poetry; Santa Fe National Historic Trail -- Poetry; Glorieta Pass (N.M.) -- Poetry; New Mexico -- Glorieta Pass; Poetry